Evaluation of the fatty liver index as a predictor for the development of diabetes among insurance beneficiaries with prediabetes. Issue 3 (10th November 2014) - Nishi, Takumi; Babazono, Akira; Maeda, Toshiki; Imatoh, Takuya; Une, Hiroshi
Abstract: Aims/Introduction: Non‐alcoholic fatty liver disease (NAFLD) is the most common liver disease in developed countries, and it was required to monitor patients with prediabetes. However, there have been few reports establishing the risk for diabetes mellitus (DM) among patients with prediabetes. The purpose of the present study was to evaluate the effect of NAFLD on the progression of DM among insurance beneficiaries with prediabetes, using data from specific health check‐ups and the fatty liver index (FLI). Materials and Methods: We used a retrospective cohort study that enrolled 967 insurance beneficiaries with prediabetes who had rarely drunk or could not drink alcohol, or whose alcohol consumption was <19 g/day from two health insurance societies. We divided insurance beneficiaries into FLI <30, intermediates FLIs and FLI ≥60, and compared the incidence rate of DM among the groups after 3 years' follow up, using multiple logistic regression models. Results: During 3 years' follow up, progression of diabetes was seen in 65 men (11.5%) and 24 women (6.0%). Logistic regression analyses showed that those with NAFLD had significantly higher risks of developing DM; this was the case in both men (odds ratio 2.68, 95% confidential interval 1.29–5.56) and women (odds ratio 10.35, 95% confidential interval 3.22–33.31). Conclusions: Among insurance beneficiaries with prediabetes, those with NAFLD had a significantly higher risk of DM than those without NAFLD. The FLI might be useful for detecting individuals who have an especially higher risk for DM, and developing more effective guidance for delivering healthcare services in Japan. Abstract : We conducted the present study to evaluate the effect of non‐alcoholic fatty liver (NAFLD) on the progression of diabetes mellitus (DM) among insurance beneficiaries with pre‐diabetes, using data from specific health check‐ups data (2008–2011) and the Fatty Liver Index (FLI). Finally, we obtained 967 study participants, as shown in Figure 1.We found that those with NAFLD had a significantly higher risk of DM than those without NAFLD. The FLI might be useful for developing more effective guidance for delivering healthcare services in Japan.